The Effect of Dates (Phoenix dactylifera) on Breast Milk Production in Post Partum Mother Day 3-9 - Rahma Kusuma Dewi; Dewi Nur Afifi; Alfika Awatiszahro; Wartinah; Dina Yulianti (Universitas STRADA Indonesia, 2021)
Mother's Milk (ASI) is the best food for babies that is produced directly from the mother's breast to her newborn baby, because its composition is appropriate for every baby's growth and development, breast milk also contains protective substances that can prevent babies from various infectious diseases . Dates contain iron, protein, fiber, glucose, vitamins, biotin, niacin, folic acid, and minerals such as calcium, sodium, and potassium which can increase breast milk production . The purpose of this study was to determine the effect of dates on breast milk production in postpartum mothers on days 3-9 at PMB Binti Qoni'ah Nganjuk 2021. The design of this study was pre-experimental using a one-group pre-posttest design. In this study obtained a population of 15 people, with a sample of 15 people using total sampling technique. The data was collected using an observation sheet and the hypothesis test used was the Wilcoxon Signed Rank Test with a significance value = 0.05. The statistical test result from the Wilcoxon Sign Rank obtained p value = 0,01 with an error level (=0.05), it can be said that p < than it can be concluded that Ho is rejected and H1 is accepted. There is an effect of dates on breast milk production in postpartum mothers on days 3 - 9 at PMB Binti Qoni'ah Nganjuk 2021. Based on the results of the study, it is hoped that the research area can be used as input for using dates to increase breast milk production in the development of traditional medicine